Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1007/s10661-010-1577-2
|View full text |Cite
|
Sign up to set email alerts
|

Industrial hygiene and toxicity studies in unorganized bone-based industrial units

Abstract: A large variety of ornamental and decorative items are manufactured from bone waste by various unorganized sectors in India. An initial survey indicated that workers were exposed at various phases of final product. The subjects (12 industrial units) were tested for total suspended particulate matter (TSPM), particulate matter <10 microm (PM(10)), and particulate matter <2.5 microm (PM(2.5)). Prevalent levels of TSPM ranged between 2.90 and 5.89 mg m(-3). Respirable fractions of occupational dust as PM(10) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…Recent epidemiological studies have found associations between increases in air particulates and increased morbidity and mortality, especially among sensitive subpopulations such as children, elderly, and those with preexisting respiratory and cardiac diseases (U.S. Environmental Protection Agency 1996). The workers are not covered by the Factory Act; therefore, they remain vulnerable to a variety of occupational hazards (Siddiqui et al 2011). Negligence of international safety and health standards for workers in the textile industry is causing the proliferation of various particulate matters which are ultimately deteriorating the health of workers.…”
Section: Introductionmentioning
confidence: 99%
“…Recent epidemiological studies have found associations between increases in air particulates and increased morbidity and mortality, especially among sensitive subpopulations such as children, elderly, and those with preexisting respiratory and cardiac diseases (U.S. Environmental Protection Agency 1996). The workers are not covered by the Factory Act; therefore, they remain vulnerable to a variety of occupational hazards (Siddiqui et al 2011). Negligence of international safety and health standards for workers in the textile industry is causing the proliferation of various particulate matters which are ultimately deteriorating the health of workers.…”
Section: Introductionmentioning
confidence: 99%
“…14 Local exhaust ventilation and exhaust hoods function by removing dust and small particles near the source, thereby decreasing the quantity of dust exposure to health care workers. 13 This research is not without limitations. One of the limitations of this study is the difference between cadaveric and living temporal bones.…”
Section: Discussionmentioning
confidence: 91%
“…While bone dust is largely composed of hydroxyapatite, it does contain trace amounts of other elements including copper, silica, iron, rubidium, and platinum. 13 The heterogeneous nature of bone dust may contribute to reports of hypersensitivity-type reactions such as asthma and anaphylaxis in individuals with frequent exposure to aerosolized bone dust from animals. 4,5 Although such cases have not been reported in health care professionals, the potential for hypersensitivity reactions is present due to the frequency to which otologic surgery is performed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations